Yobel: Periode, Sosial, Ekonomi, dan Teologi - Laoly, Nepho Gerson (KERUGMA: Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
The literature on Jubilees discussesÂ implications of acquiring the Land of Canaan (Palestine). Jubilee had a high degree of law in aspects of The Life of the Israelites, especially the administrating of the territory of the land of Canaan.Â  However, there are also scholars who think of jubilees as a rule instituted by priests in the period of exile or in the period of return from exile. Jubilee writing is in the background of the Ancient Near East, the Second Temple, and the writing of the gospels that use jubilee years such as Luke.Â  In addition, jubilees are the basic arguments for liberating and socialist theology or related to contemporary agendas that use the word "independence" and the like. Jubilees cover four categories: period, social, economic, and theological categories.Â  Research is conducted to gain a comprehensive understanding of jubilees through literature surveys in biblical, socio-economic, and archaeological areas. Qualitative methods are applied to accommodate various jubilee-related information in providing Jubilee exposition material. The application of close reading is done in order to get the right information. Archaeology is also a secondary source to sharpen this research.Keywords: Jubilee; Ancient Near East; Biblical; Social-Economy; LiberationÂ Â Abstrak:Literatur mengenai Yobel membicarakan implikasi dari mengakuisisi daratan Kanaan (Palestina). Yobel memiliki derajat hukum yang tinggi dalam aspek kehidupan bangsa Israel, terutama pengadministrasian wilayah tanah Kanaan. Kendati demikian ada juga para sarjana yang beranggapan Yobel sebagai suatu aturan yang dilembagakan oleh para imam pada periode pembuangan ataupun dalam periode kembali dari pembuangan. Penulisan Yobel ada di dalam latar belakang Timur Dekat Kuno, Bait Allah Kedua, dan penulisan injil yang menggunakan tahun Yobel seperti Lukas.Â  Selain itu Yobel menjadi argumen dasar bagi teologi-teologi yang bersifat pembebasan dan sosialis, ataupun terkait dengan agenda kontemporer yang menggunakan kata â€œkemerdekaanâ€ dan sejenisnya. Yobel mencakup empat kategori yaitu kategori periode, sosial, ekonomi, dan teologi.Â  Penelitian dilakukan untuk mendapatkan pemahaman Yobel yang komprehensif melalui survey literatur pada area biblika, sosial-ekonomi, dan arkeologi. Metode kualitatif diterapkan untuk menampung berbagai informasi terkait Yobel dalam menyediakan materi eksposisi Yobel. Penerapan close readingÂ  dilakukan agar mendapatkan informasi yang tepat. Arkeologi juga menjadi sumber sekunder untuk mempertajam penelitian ini.Kata Kunci: Yobel; Timur Dekat Kuno; Biblika; Sosial; Ekonomi; Pembebasan